Effect of nano composite boron carbide on the mechanical and corrosion behaviour of aluminium matrix composite - Zaifol Samsu; Norinsan Kamil Othman; Mohd Suzeren Md Jamil; Hafizal Yazid; Mohd Sofian Alias (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study examined the use of stir casting to create an aluminum-nanoscale boron carbide composite. Following the sample’s solidification, mechanical and physical tests are carried out to determine the density and hardness. Tafel polarization in a 3.5% NaCl solution was utilized to determine the composite’s corrosion behavior, and tensile strength and hardness characterization techniques were employed to determine its mechanical characteristics. After the stir casting process, the surface morphology of the metal and the dispersion of boron carbide particles on the matrix were examined using a field emission scanning electron microscope (SEM). The obtained powders and matrix samples were examined using X-ray diffraction (XRD) analysis to determine the phase and if reinforcement particles (B4C) were present in the composite samples. The mechanical, microstructural, and corrosion investigations were used to evaluate the performance of the composites. The homogeneous distribution of the reinforcing particle was observed by the inspection of micrographs. The results showed that the corrosion rate of the aluminium matrix composite was lower than that of the base alloy in a 3.5% NaCl solution. Simultaneously, the composite’s corrosion rates escalated as the B4C concentration in the aluminum matrix grew. Hardness investigation has demonstrated that an increase of B4C content in the aluminium matrix enhanced the hardness rating. In the tensile test, the composite containing 0.8 weight percent B4C achieved a maximum strength of 149.95 MPa, which was roughly 48.64 MPa (32%) greater than the basic alloy.